PEMETAAN ZONASI HARGA LAHAN SEBELUM DAN SESUDAH BERDIRINYA UIN IMAM BONJOL DI KELURAHAN BALAI GADANG KECAMATAN KOTO TANGAH KOTA PADANG - Ratna Wahyu Kusuma Arum; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2020)
Abstract This research of aims are: 1) know the pattern of zoning changes in land prices around UIN Imam Bonjol related before and after the existence of Imam Bonjol UIN. 2) know the factors that influence the price of land around UIN Imam Bonjol related before and after the existence of Imam Bonjol UIN. This type of research is descriptive with a quantitative approach. In analyzing patterns of changes in land prices, researchers used the Total Sampling technique and conducted interviews in the field. The result of this research is a map of land price patterns which shows that the closer to Imam Bonjol UIN, the land prices are getting more This happens because of influencing factors such as land ownership, slope, public utilities, and accessibility. With the establishment of Imam Bonjol UIN, the government has begun to improve road access and public utilities, as well as many people who have started to take care of their ownership certificates. And a lot of community land is used as boarding houses, food stalls, photocopies and laundry.